2020
DOI: 10.1101/2020.01.31.928770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consequences of single-locus and tightly linked genomic architectures for evolutionary responses to environmental change

Abstract: Genetic and genomic architectures of traits under selection are key factors influencing evolutionary responses. Yet, knowledge of their impacts has been limited by a widespread assumption that most traits are controlled by unlinked polygenic architectures. Recent advances in genome sequencing and eco-evolutionary modelling are unlocking the potential for integrating genomic information into predictions of population responses to environmental change. Using eco-evolutionary simulations, we demonstrate that hypo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 138 publications
0
28
0
Order By: Relevance
“…A large body of work has shown the relevance of genetic architecture in determining evolutionary responses [60][61][62][63][64][65][66][67][68]. Recent works highlight the relevance of the genetic architecture underlying fitness traits when predicting a population's response to environmental changes [69] and selective pressures such a fishing [70]. Future work elucidating how such mixed genetic architectures affect predicted evolution of traits, compared to that of omnigenic or polygenic architectures, will be valuable.…”
Section: Multi-snp Associations Identified Using Pimassmentioning
confidence: 99%
“…A large body of work has shown the relevance of genetic architecture in determining evolutionary responses [60][61][62][63][64][65][66][67][68]. Recent works highlight the relevance of the genetic architecture underlying fitness traits when predicting a population's response to environmental changes [69] and selective pressures such a fishing [70]. Future work elucidating how such mixed genetic architectures affect predicted evolution of traits, compared to that of omnigenic or polygenic architectures, will be valuable.…”
Section: Multi-snp Associations Identified Using Pimassmentioning
confidence: 99%
“…As in S. uniflora, those species that evolved to survive in environments with natural sources of high abiotic stress, but which do not compete well in low-abiotic stress/high-biotic competition environments, may be particularly well suited to cope with the ongoing human modification of the planet. Alongside evidence of widespread local adaptation to different environmental conditions in other species (Fournier-Level et al 2011;Papadopulos et al 2014), our findings indicate that while it may be possible to predict which species will adapt to specific environments, the underlying genetic basis to that adaptation may be considerably more variable than is currently understood from the limited number of well-studied examples (Oomen et al 2020). In order to be accurate, predictions of evolutionary responses to environmental change from genomic data will need to account for the possibility that multiple genetic architectures can produce similar phenotypic responses.…”
Section: Resultsmentioning
confidence: 72%
“…To test whether population pairs in more ecologically similar habitats exhibit higher degrees of convergence, we measured aspects of water quality in situ (temperature, pH, specific conductivity, dissolved oxygen, and H2S concentration) and downloaded 19 geospatial variables that describe climatic variation for each sulfide spring (28). Principal component (PC) analysis indicated that different springs primarily segregated along the first PC axis (Figure 2C), which was correlated with temperature, pH, and H2S concentration, as well as bioclimatic variables 1,4,6,7,9,11,12,13,14,16,17,18, and 19 (correlations: |0.20| < r < |0.28|; Table S1). In general, sulfide springs in Mexico (negative scores along PC axis 1) exhibited higher temperatures and H2S concentrations, lower pH, less seasonality, and more precipitation compared to the springs in Florida and the Dominican Republic (positive scores along PC axis 1).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, unique, lineage-specific evolutionary outcomes in response to apparently similar selective regimes can arise through a multitude of genetic, functional, and ecological mechanisms (11). For example, differences in genetic architecture can bias responses to selection (12), functional redundancy can cause equivalent fitness by alternative means (13), and cryptic ecological differences among lineages can select for different phenotypic optima (14). Still, attempts to explain the degree of convergent and lineage-specific ( i.e ., nonconvergent) evolutionary patterns remain scarce.…”
Section: Introductionmentioning
confidence: 99%